Multimodal cohesion and viewers' comprehension of scene transitions in film: an empirical investigation - Markhabayeva, Dayana; Tseng, Chiao-I (Frontiers in Communication, 2024)
This paper presents three empirical studies that unravel how the devices of multimodal cohesion support viewers' narrative interpretation of scene transitions in film. The linguistics-informed method of cohesion analysis in film uncovers the establishment of cohesive ties between characters, objects, settings and characters' actions. Previous studies using eye-tracking and comprehension tests already indicate the significance of multimodal cohesion in people's comprehension of background settings within a continuous scene. The present paper investigates further whether film cohesion impacts viewers´story comprehension across different scenes and settings. Moreover, it also explores whether the spatio-temporal relations between scenes theorised by Bateman ( 2007) is a significant factor, along with cohesive devices, in viewers' scene comprehension.Methodologically, we create contrasting film situations by manipulating cohesion structures and spatio-temporal orders of scenes. Our comparative analyses of viewers' comprehension of these different film situations reveal that the presence of cohesive cues significantly can influence viewers' accurate scene comprehension. Through testing the inter-relation of cohesion, spatio-temporal order, characters' intention and viewers' time perception, this paper offers new avenues for further exploration of space, time and coherence in film.